Partially Hydrolysed Whey Has Superior Allergy Preventive Capacity Compared to Intact Whey Regardless of Amoxicillin Administration in Brown Norway Rats - Graversen, Katrine Bækby; Larsen, Jeppe Madura; Pedersen, Signe Schultz; Sørensen, Laila Vestergaard; Christoffersen, Heidi Frahm; Jacobsen, Lotte Neergaard; Halken, Susanne; Licht, Tine Rask; Bahl, Martin Iain; Bøgh, Katrine Lindholm (Frontiers in Immunology, 2021)
Background: It remains largely unknown how physicochemical properties of hydrolysed infant formulas influence their allergy preventive capacity, and results from clinical and animal studies comparing the preventive capacity of hydrolysed infant formula with conventional infant formula are inconclusive. Thus, the use of hydrolysed infant formula for allergy prevention in atopy-prone infants is highly debated. Furthermore, knowledge on how gut microbiota influences allergy prevention remains scarce. Objective: To gain knowledge on (1) how physicochemical properties of hydrolysed whey products influence the allergy preventive capacity, (2) whether host microbiota disturbance influences allergy prevention, and (3) to what extent hydrolysed whey products influence gut microbiota composition. Methods: The preventive capacity of four different ad libitum administered whey products was investigated in Brown Norway rats with either a conventional or an amoxicillin-disturbed gut microbiota. The preventive capacity of products was evaluated as the capacity to reduce whey-specific sensitisation and allergic reactions to intact whey after intraperitoneal post-immunisations with intact whey. Additionally, the direct effect of the whey products on the growth of gut bacteria derived from healthy human infant donors was evaluated by in vitro incubation. Results: Two partially hydrolysed whey products with different physicochemical characteristics were found to be superior in preventing whey-specific sensitisation compared to intact and extensively hydrolysed whey products. Daily oral amoxicillin administration, initiated one week prior to intervention with whey products, disturbed the gut microbiota but did not impair the prevention of whey-specific sensitisation. The in vitro incubation of infant faecal samples with whey products indicated that partially hydrolysed whey products might confer a selective advantage to enterococci. Conclusions: Our results support the use of partially hydrolysed whey products for prevention of cow’s milk allergy in atopy-predisposed infants regardless of their microbiota status. However, possible direct effects of partially hydrolysed whey products on gut microbiota composition warrants further investigation.